2019
DOI: 10.1609/aaai.v33i01.33017984
|View full text |Cite
|
Sign up to set email alerts
|

Counting and Sampling Markov Equivalent Directed Acyclic Graphs

Abstract: Exploring directed acyclic graphs (DAGs) in a Markov equivalence class is pivotal to infer causal effects or to discover the causal DAG via appropriate interventional data. We consider counting and uniform sampling of DAGs that are Markov equivalent to a given DAG. These problems efficiently reduce to counting the moral acyclic orientations of a given undirected connected chordal graph on n vertices, for which we give two algorithms. Our first algorithm requires O(2nn4) arithmetic operations, improving a previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…We gave an exact algorithm that is able to compute the posterior of causal effects for data sets of realistic size, with up to around 20 variables. This scaling is similar to the scaling of other exact exponential algorithms for BMA over structures in graphical models, a topic of active research (see, e.g., Koivisto and Sood 2004;Tian and He 2009;Tian, He, and Ram 2010;Parviainen and Koivisto 2011;Chen and Tian 2014;Kangas, Niinimäki, and Koivisto 2015;Talvitie and Koivisto 2019). With a small modification to our approach for computing parent set posteriors, we obtained a variant that is currently the fastest known algorithm for computing ancestor relation posterior probabilities (Chen, Meng, and Tian 2015).…”
Section: Discussionsupporting
confidence: 68%
“…We gave an exact algorithm that is able to compute the posterior of causal effects for data sets of realistic size, with up to around 20 variables. This scaling is similar to the scaling of other exact exponential algorithms for BMA over structures in graphical models, a topic of active research (see, e.g., Koivisto and Sood 2004;Tian and He 2009;Tian, He, and Ram 2010;Parviainen and Koivisto 2011;Chen and Tian 2014;Kangas, Niinimäki, and Koivisto 2015;Talvitie and Koivisto 2019). With a small modification to our approach for computing parent set posteriors, we obtained a variant that is currently the fastest known algorithm for computing ancestor relation posterior probabilities (Chen, Meng, and Tian 2015).…”
Section: Discussionsupporting
confidence: 68%
“…is the number of MAOs when we add m dominating vertices. • Dynamic Programming in Tree Decomposition: The algorithm by Talvitie and Koivisto (2019) based on dynamic programming on the clique-tree with time-complexity in O(2 k k!k 2 n) parameterised by the treewidth k. We implemented 2 AnonMAO using C++, and for the other algorithms, we used the C++ implementations of Talvitie and Koivisto (2019). All the implementations use only one thread of execution and compute the result exactly.…”
Section: Resultsmentioning
confidence: 99%
“…Talvitie and Koivisto (2019) observed that each UCCG considered in the RootPicking algorithm is an induced subgraph of the original UCCG. By memoizing the results, they reduced the time complexity toÕ(2 n ) and also achieved speedups in practice (Talvitie and Koivisto 2019). He and Yu (2016) extended the RootPicking algorithm to better handle dense graphs.…”
Section: Return Solmentioning
confidence: 99%
See 1 more Smart Citation
“…Chordal graphs arise in practical applications from a wide variety of fields, such as database management, computer vision, and Bayesian networks. Counting Markov equivalent DAGs in chordal graphs plays an important role in structural learning of Bayesian networks (Ghassami et al 2019;Talvitie and Koivisto 2019). Generating chordal graphs uniformly at random is necessary for testing the performance of those algorithms.…”
Section: Introductionmentioning
confidence: 99%